The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/glia.21048
|View full text |Cite
|
Sign up to set email alerts
|

Human remyelination promoting antibody inhibits apoptotic signaling and differentiation through Lyn kinase in primary rat oligodendrocytes

Abstract: Purpose-Human remyelination promoting IgM mAbs target oligodendrocytes (OLs) and function in animal models of multiple sclerosis (MS). However, their mechanism of action is unknown. This study seeks to identify the cellular mechanism of action of a recombinant human IgM on OL survival.Methods-Binding of rHIgM22 to the surface of rat OLs was studied by co-localization with various markers. RHIgM22-mediated effects on apoptotic signaling in OLs, differentiation markers and signaling molecules were detected by We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 45 publications
3
53
0
1
Order By: Relevance
“…However, it is clear that the antigen(s) of IgM22 can be presented to activate natural IgM production without inducing autoimmunity. As previously mentioned, HIgM22 can mediate signaling to promote oligodendrocyte precursor cell proliferation in cultured mixed glia [86] and accelerate myelin repair in vivo [4]. This finding has provided evidence that, in addition to regulating the immune system, natural IgMs signal the neural cells directly and/or indirectly to mediate a novel CNS function distinctive to the traditional view of natural IgMs in maintaining homeostasis.…”
Section: Neural Reactive Natural Igms and The Nature Of Neural Surface mentioning
confidence: 79%
“…However, it is clear that the antigen(s) of IgM22 can be presented to activate natural IgM production without inducing autoimmunity. As previously mentioned, HIgM22 can mediate signaling to promote oligodendrocyte precursor cell proliferation in cultured mixed glia [86] and accelerate myelin repair in vivo [4]. This finding has provided evidence that, in addition to regulating the immune system, natural IgMs signal the neural cells directly and/or indirectly to mediate a novel CNS function distinctive to the traditional view of natural IgMs in maintaining homeostasis.…”
Section: Neural Reactive Natural Igms and The Nature Of Neural Surface mentioning
confidence: 79%
“…The impact of these molecules on OPCs remains controversial, with reports suggesting both a beneficial outcome on myelination and induction of OPC death. For example, TNFα is highly expressed in demyelinating MS lesions and has been shown to potentiate IFN-γ-induced cell death in vitro (Andrews et al, 1998; Watzlawik et al, 2010). Arnett et al showed a modest delay in cuprizone-induced oligodendrocyte death in TNF-α knockout mice, implicating it as a potentially harmful cytokine (Arnett et al, 2001).…”
Section: Opc As Innate Immune Cellsmentioning
confidence: 99%
“…rHIgM22 is a true human monoclonal antibody that crosses the blood brain barrier [23,24] and targets demyelinating lesions [25]. This antibody increases Ca 2+ signaling in oligodendrocytes and astrocytes [26] stimulates proliferation of progenitor oligodendrocytes by reorganizing plasma membranes of oligodendrocyte surfaces and inducing a signaling complex [27]. In contrast, rHIgM12 binds to neurons and protects against axonal injury in chronic TMEV murine model and ALS model [12].…”
Section: Discussionmentioning
confidence: 99%